Epidermal focusing of light and modelling of reflectance infloral-petals with conically shaped epidermal cells - Gkikas, Dimitrios; Apostolos Argiropoulos; Sophia Rhizopoulou (Flora, 2015)
A model of floral reflectance of petals with conically-shaped epidermal cells is presented for Nerium oleander and Oxalis pes-caprae. The model was achieved by combined microscopic-scale structures and optical properties of petals; the model theory was based on concepts of physical laws, analytic geometry, vector analysis and micro-optics. The model is shown to fit experimental data of floral reflectance. Conically shaped, adaxial, epidermal cells of petals have focal regions, where incident light rays are focused on the centre of cells. Within tissues light is selectively channelled into sites containing light absorbing pigments. Particular attention was given to consequences of focusing of light within conical, epidermal cells of petals with respect to blossoming regulated by photoperiod, which acts to insure that flower opening occurs during suitable, environmental conditions.